Correlation between Body Mass Index and Body Fat Percentage - Muhammad Ilman; Yenni Zuhairini; Amillia Siddiq (Althea Medical Journal, 2015)
Background: Body mass index (BMI) has been used to determine the nutritional status which is classified into low, normal, overweight or obese. The BMI only shows a comparison of height and weight instead of body composition which consists of fat mass and fat–free mass. Most of people assumed that BMI overage means fat mass overage as well, yet it does not occur in all cases. This study was conducted to measure the correlation between BMI and body fat percentage.Methods: An analytical study was conducted to 100 male and female students respectively from Universitas Padjadjaran Jatinangor batch 2009 to 2013. The body  weight was measured using scales , whereas the body height was measured using stature meter. The body fat percentage was measured using Bioelectrical Impedance Analysis (BIA). The BMI was calculated by dividing the body weight in kilogram divided by body height in meter square. Data was collected from September to October 2013 and analyzed by Pearson’s correlation test.Results: The mean of BMI in male students and female students were 22.56 and 21.35 respectively. The body fat percentage was 16.44 for men and 28.09 for women. Correlation score between BMI and fat mass in male students were 0.853 and female students are 0.834.Conclusions: There is a strong and positive correlation between BMI and body fat percentage both in male and female students in Universitas Padjadjaran Jatinangor. Among this population, BMI can still be used todetermine body fat percentage. [AMJ.2015;2(4):575–8] DOI: 10.15850/amj.v2n4.642